FEATURES OF THE USE OF NEW EDUCATIONAL TECHNOLOGIES IN THE PSYCHOLOGICAL PREPARATION OF CHILDREN FOR SCHOOL (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article says that psychological preparation of a child for school is not only the formation of a certain level of knowledge, skills, and abilities, but also the formation of personal, intellectual, motivational, emotional, volitional, and communicative qualities that ensure the success of the educational process. At the same time, it was emphasized that a parent and a school preparation specialist will play a key role in preparing for school, and the use of new educational technologies in the preparation process is a key condition for psychological readiness.